2020
DOI: 10.3390/ijerph17176372
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms and Feeding Problems and Their Associations with Dietary Interventions, Food Supplement Use, and Behavioral Characteristics in a Sample of Children and Adolescents with Autism Spectrum Disorders

Abstract: Autism spectrum disorders (ASD) are characterized by impairments in social interaction, communication, and restricted, stereotyped behavior. Gastrointestinal (GI), nutritional, and feeding problems are often reported in ASD. We investigated the prevalence of GI symptoms, food selectivity, and mealtime difficulties, and their associations with dietary interventions, food supplement use, and behavioral characteristics in a sample involving 247 participants with ASD and 267 controls aged 2–18 years. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 64 publications
(119 reference statements)
4
34
0
4
Order By: Relevance
“…FED is also associated with cognitive deficits, which in turn increased the risk of ID ( 29 , 30 ). Additionally, FED has associated with physical issues, such as neuromuscular disorders, gastrointestinal disorders, and food allergies, which contribute to the development of neurodevelopmental disorders ( 31 , 32 ). This study expands our understanding by indicating that children with FED have an increased risk of a wide range of neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…FED is also associated with cognitive deficits, which in turn increased the risk of ID ( 29 , 30 ). Additionally, FED has associated with physical issues, such as neuromuscular disorders, gastrointestinal disorders, and food allergies, which contribute to the development of neurodevelopmental disorders ( 31 , 32 ). This study expands our understanding by indicating that children with FED have an increased risk of a wide range of neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies from the current review include a report [ 15 ] of a higher frequency of constipation in children with ASD, a study [ 16 ] which found children with ASD and regression more often had abnormal stool than those without regression, and another experiment [ 17 ] which found GI symptoms to be more common in children and adolescents with ASD than in TD controls, and for these symptoms to be weakly correlated to behavioural measures. Correlations such as these have been documented elsewhere [ 18 , 19 , 20 ].…”
Section: Gastrointestinal Symptoms In Asdmentioning
confidence: 99%
“…Correlations such as these have been documented elsewhere [ 18 , 19 , 20 ]. These studies reference the often non-specific nature of GI symptoms with one explaining that “a GI pathology specific to ASD had not been established” (Babinska et al, 2020 [ 17 ]). Regardless, a notable body of literature has investigated for a comorbidity between ASD and specific GI conditions, often finding significant results.…”
Section: Gastrointestinal Symptoms In Asdmentioning
confidence: 99%
“…Currently, the physiological basis/es for eating difficulties in individuals with ASD is not well understood and is plagued by heterogeneity both in study design and how symptoms manifest across the spectrum (Margari et al, 2020). Recent studies show that while children with ASD are generally pickier about their food than neurotypical children (Babinska et al, 2020;Li C. et al, 2020), other symptoms may be unique to specific genetic forms of ASD. For example, in people with SYNGAP1 mutations, there is a correlation between eating and seizures (Vlaskamp et al, 2019).…”
Section: Setting the Stagementioning
confidence: 99%